New anti-Alzheimer drugs from biodiversity: the role of the natural acetylcholinesterase inhibitors - Viegas, C.; Bolzani, Vanderlan da Silva [UNESP]; Barreiro, E. J.; Fraga, CAM (Bentham Science Publ Ltd, 2005)
Alzheimer's disease (AD) is a progressive neurodegenerative pathology with severe economic and social impact. There is currently no cure, although cholinesterase inhibitors provide effective temporary relief of symptoms in some patients. Nowadays, drug research and development are based on the cholinergic hypothesis that supports the cognition improvement by regulation of the synthesis and release of acetylcholine in the brain. There are only four commercial medicines approved for treatment of AD, and natural products have played an important alternative role in the research for new acetylcholinesterase inhibitors, as exemplified through the discovery of galantamine. This profile conducts us to give in this paper an overview relating the several classes of natural products with anti-cholinesterasic activity as potential templates to the design of new selective and powerful anti-Alzheimer drugs.